Virus-induced gene silencing of SlPYL4 decreases the drought tolerance of tomato - Yue Li (Horticultural Plant Journal, 2022)
The abscisic acid (ABA) receptor PYR/PYL/RCAR, located upstream of the ABA signaling pathway, recognizes ABA signals and initiates the primary process of signal transduction. In our previous study, we found that the PYL4 gene in tomato plants was significantly upregulated after exogenous treatment with the hormone ABA. The present study used virus-induced gene silencing (VIGS) to further elucidate the role of the PYL4 gene in response to drought in tomato (Solanum lycopersicum) plants. Under the drought treatment, the SlPYL4-silenced plants wilted faster than the control plants did. Physiological indicators showed that the total reactive oxygen species (ROS) content and superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) activities of the SlPYL4-silenced plants were lower than those of the control plants after 3 and 6 h of drought stress treatment. After 3 h of drought treatment, hydrogen peroxide (H2O2) and superoxide anion (O2−.) accumulated much more in the leaves of the SlPYL4-silenced plants than in the leaves of the control plants. These results indicated that PYL4 plays a positive role in drought tolerance in tomato plants. Our results also suggest that SlPYL4 is located upstream of the ABA pathway to regulate the expression of PP2C, SnRK, and AREB/ABF genes.